3K3A-Activated Protein C Variant Does Not Interfere With the Plasma Clot Lysis Activity of Tenecteplase. Issue 7 (July 2020) - Mukherjee, Purba; Lyden, Patrick; Fernández, José A.; Davis, Thomas P.; Pryor, Kent E.; Zlokovic, Berislav V.; Griffin, John H.
Abstract : Background and Purpose: A recombinant engineered variant of APC (activated protein C), 3K3A-APC, lacks anticoagulant properties (<10%) while preserving APCs anti-inflammatory, anti-apoptotic, and neuroprotective functions and is very promising in clinical trials for ischemic stroke. Therapeutic intervention with single bolus administration of the third-generation tPA (tissue-type plasminogen activator), tenecteplase, is anticipated to be widely adopted for treatment of acute ischemic stroke. 3K3A-APC is well-tolerated in stroke patients dosed with alteplase, and in vitro studies show 3K3A-APC does not interfere with alteplase-induced clot lysis. The purpose of this in vitro study was to assess the influence of 3K3A-APC on tenecteplase-induced clot lysis. Methods: Tenecteplase-mediated lysis of thrombin generated plasma clots of human normal pooled plasma was monitored in the presence of varying doses of 3K3A-APC. The effects on fibrinolysis by tenecteplase and alteplase were compared. Results: The presence of 3K3A-APC shortened the time for clot lysis induced by tenecteplase at very low levels but not at higher therapeutic concentrations of tenecteplase. Comparisons of alteplase-mediated clot lysis to tenecteplase clot lysis showed that both thrombolytic agents behaved similarly in the presence of 3K3A-APC. Conclusions: These results indicate that 3K3A-APC does not interfere with tenecteplase's clot lysis function.